RNA-based therapies for neurodevelopmental disorders: innovative tools for molecular correction - Drongitis, Denise; Verrillo, Lucia; de Bellis, Alberto; Miano, Maria Giuseppina (Frontiers in Molecular Biosciences, 2025)
Modulation of RNA and protein expression to restore or normalize neuronal function has emerged as a powerful therapeutic strategy for neurodevelopmental disorders (NDDs) tailoring individual genetic mutations causing intellectual disability (ID), or autism spectrum disorder (ASD), or developmental epileptic encephalopathy (DEE). In recent years, diverse classes of RNA-based molecules have been developed with therapeutic potential, including antisense oligonucleotides (ASOs), oligonucleotides targeting natural antisense transcripts (antagoNATs), Short Interspersed Nuclear Element UP-regulating RNAs (SINEUPs), interfering RNAs (RNAi), Exon-Specific engineering U1 small nuclear RNAs (ExSpeU1s), and small-activating RNA (saRNA) This review highlights the promising advances of these RNA-based therapeutics in addressing syndromic ID, such as Fragile X syndrome, MECP2 duplication syndrome, FOXG1-gene related Rett syndrome and Angelman syndrome, which are characterized by well-defined genetic mutations with limited treatment options. Moreover, ASD-related condition linked to mutations in CHD8 is under investigation, extending the therapeutic landscape to complex behavioral and cognitive disorders. In the same way, several DEEs caused by mutations in CDKL5, DNM1, KCNT1, SCN1A, SCN2A, SCN8A, and UBA5 genes, which present severe pharmaco-resistant epilepsy, are increasingly becoming targets for RNA molecules that aim to restore neuronal excitability and network function. Together, these findings underscore the expanding therapeutic landscape enabled by RNA technologies, offering unprecedented specificity and flexibility for gene-targeted interventions in NDDs. As the field of RNA medicine continues to evolve across genomics and neuroscience, we aim to provide a resource for researchers and clinicians on promising innovative tools for molecular correction.